Functional activity of the H3.3 histone chaperone complex HIRA requires trimerization of the HIRA subunit - Dominique Ray-Gallet (Nature Portfolio, 2018)
The HIRA histone chaperone complex is involved in the deposition of the histone variant H3.3. Here the authors, by using biochemical and crystallographic approaches, report the homotrimerization of the HIRA subunit which is critical for the functional activity of the complex.